Study of Morphological Characteristics of Cryopreserved Cell Cultures of Stromal Origin - Volkova, N O. (Problems of Cryobiology and Cryomedicine, 2012)
Mesenchymal stromal cells (MSCs) of bone marrow and chorion cell culture (CCC) were cryopreserved under protection of 10% DMSO and 20% fetal bovine serum using low cooling rate (1 deg/min) down to â€“80Â°C with following plunging into liquid nitrogen. The findings have shown than after low temperature storage both studied cultures kept the ability to proliferation and directed differentiation. Chorion cell culture was characterized with higher proliferative activity if compared with bone marrow MSCs. The ability to the directed differentiation towards adipo- and chondrogeneic lineages was higher for bone marrow MSCs versus CCC.